C. elegans as Model for Drug Discovery - Carretero, Maria; M. Solis, Gregory; Petrascheck, Michael (Current Topics in Medicinal Chemistry, 2017)
Small molecule screens using C. elegans as a model are becoming increasingly popular as the number of high-throughput methodologies has steadily increased over the years. Here we focus on the biology that underlies this increased popularity and outline the reasons that make C. elegans an attractive model for drug discovery. We discuss successful C. elegans based drug discovery projects in the literature and future challenges ahead.
Keywords: Drug discovery